The UK Environmental Change Network after twenty years of integrated ecosystem assessment: Key findings and future perspectives. (September 2016) - Sier, Andrew; Monteith, Don
Highlights: The UK Environmental Change Network has been in operation for 20 years. The ECN addresses the causes and consequences of environmental change. The range of papers in this issue illustrates wide applicability of the network. Tighter integration with complementary programmes is highly desirable. Evolving environmental challenges will require network development and adaptation. Abstract: The UK Environmental Change Network (ECN), the UK's Long-Term Ecosystem Research (LTER) network, has now been operating for over twenty years. It was established in 1992 as a set of terrestrial sites at which sustained observations relevant to a range of ecological indicators and environmental parameters could be made. An additional ECN freshwater network was launched in 1994. In this paper we provide a brief history of the network, and describe its current structure and role within a complementary wider range of UK environmental monitoring and observation programmes that are either more focussed on specific parameters or habitats, or operate at different temporal and spatial scales. We then provide a review of the other papers within this Special Issue, which exemplifies the broad range of environmental concerns that ECN data and sites are helping to address. These include network-wide summaries of environmental and biological trends over the first two decades of monitoring, more site-specific assessment of the ecological impacts of local pressures resulting from changes in management, biological and ecosystem service indicator development, and the testing of new monitoring technologies. We go on to consider: (i) future directions of network development and adaptation in light of recently emerging environmental concerns, dwindling financial resources and the consequent need for greater efficiency; (ii) the desire for tighter integration with other monitoring and observation programmes both nationally internationally; (iii) opportunities raised by recent technological developments; and (iv) the need to process and make available data more rapidly to increase the capacity of ECN sites as early warning systems. In its first two decades of operation the ECN has accumulated a robust set of baseline data that describe environmental and biological variability across a range of habitats in unprecedented detail. With appropriate, informed development, these should prove invaluable in discerning the causes and consequences of environmental change for decades to come.